Study on Structural Health Monitoring of Offshore Structure using Fiber-Bragg Grating Sensors - A/P Gurdev Singh, Rajvinder Kaur (IRC, 2019)
Structural Health Monitoring is a continuous observation on structures to observe and identify anomalies. In the process the use of non-destructive technique and sensing method for structural characteristics; also referring to its structural response to detect any changes that may show any sign of degradation or damages is typically conducted. The detection of these damages is important as it can alert if these changes will cause harm.